Study on high temperature sealing behavior of packer rubber tube based on thermal aging experiments. (January 2020) - Dong, Liangliang; Li, Kun; Zhu, Xiaohua; Li, Zongqi; Zhang, Daopeng; Pan, Yong; Chen, Xiaowen
Highlights: Packer rubber thermal aging experiments were carried out and the setting model of packer rubber tube was established. It was pointed out that the Yeoh model was more suitable for the material constitutive of the packer tube under high temperature conditions. Analyzed the sealing performance and strength behavior of packer in high temperature condition. Sensitivity analysis of packer rubber key parameters was carried out. Abstract: With the exploration and development of high temperature oil and gas wells, high temperature working conditions have gradually become the new normal state of drilling and completion engineering. Due to the high temperature, the failure of the packer rubber seal and the crushing seriously affect the normal development of oil and gas fields. This paper, aiming at the seal failure of rubber tude at high temperature, the parameters of the constitutive model of rubber tude were studied through the rubber thermal aging experiments. And the finite element calculation model of the packer under the sitting condition was established. The effect of temperature load on the sealing performance and strength behavior of packer rubber was studied. The effect of key parameters of the rubber tube-casing gap δ, the dip angle α of the adjacent rubber tube contact surface and the initial setting load on the sealing performance of the packer under high temperature conditions were analyzed. The findings show that the Yeoh model is more suitable to describe the high temperature material constitutive structure of the packer tube; At high temperature, the larger the gap δ is, the worse the packer sealing performance is; While 12–24° for angle α, sealing performance is better; The suggested initial setting limit load for packer rubber tube safety seal is 68–76 kN. The research work in this paper is of great significance to the design of packer rubber tube structure and its adaptability to high temperature conditions.